Automated Fabrication of 2‐nm Solid‐State Nanopores for Nucleic Acid Analysis. Issue 10 (2nd March 2014) - Briggs, Kyle; Kwok, Harold; Tabard‐Cossa, Vincent
<x xml:space="preserve">Abstract</x> We demonstrate the automated and reproducible fabrication of sub‐2‐nm nanopores in 10‐nm thick silicon nitride membranes, through controlled dielectric breakdown in solution. Our results reveal that under the appropriate conditions, nanopores can be fabricated with a size no larger than 2.0 ± 0.5‐nm in diameter for a sample of N = 23 nanopores, with an average and standard deviation of 1.3 ± 0.6‐nm. The dimensions of these nanopores are confirmed by using individual translocating DNA molecules as molecular rulers. We show that a 2.0‐nm and a 2.1‐nm diameter nanopore are capable of distinguishing single‐stranded DNA versus double‐stranded DNA, and that a 2.4‐nm diameter nanopore can be used to investigate the overstretching transition in short dsDNA fragments. These results highlight the reliability and precision of the automated fabrication of nanopores via controlled dielectric breakdown, showing great promise for the manufacturing of future nanopore‐based technologies.